A new species of Sibon (Squamata: Colubridae) from the mountains of eastern Guatemala - Rovito, Sean M.; Papenfuss, Theodore J.; Vásquez-Almazán, Carlos R. (Zootaxa, 2012)
A new species of snake of the genus Sibon (Squamata: Colubridae) is described from La Montaña de las Granadillas, partof the Sierra del Merendón in eastern Guatemala. Sibon merendonensis is part of the S. annulatus group, and differs fromother members of the group in its scale row formula, head scalation and body size. The new species is known only from the holotype and was collected from an isolated area of cloud forest near Zacapa, Department of Zacapa, Guatemala.